Pendidikan Karakter Terintegrasi Keterampilan Abad Ke-21 - Zubaidah, Siti (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: The 21st Century Skills Integration on Character Education]. Various cases carried out by teenagers require serious handling with a variety of strategies, including through character education. Character education does not mean reducing or replacing "traditional" educational goals such as the accumulation of knowledge and the development of intellectual and practical abilities. Character education is carried out integrated into every subject and requires the support of all parties: parents, teachers, schools, education staff, the daily community of students and of course the government. The development of character can be understood in a model, including the Neo-Aristotelian Model. Good character education will not only affect well being and good character, but also good academic ability. Character education is not something new, and it is not separated from the 21st-century skill-building needed today.